2020
DOI: 10.1002/ange.202006842
|View full text |Cite
|
Sign up to set email alerts
|

CO2‐Folded Single‐Chain Nanoparticles as Recyclable, Improved Carboxylase Mimics

Abstract: Emulating the function of natural carboxylases to convert CO 2 under atmospheric condition is a great challenge. Herein we report a class of CO 2-folded single-chain nanoparticles (SCNPs) that can function as recyclable, functionintensified carboxylase mimics. Lewis pair polymers containing bulky Lewis acidic and basic groups as the precursor, can bind CO 2 to drive an intramolecular folding into SCNPs, in which CO 2 as the folded nodes can form gas-bridged bonds. Such bridging linkages highly activate CO 2 , … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 46 publications
0
1
0
Order By: Relevance
“…More recently, SCPNs were reported that efficiently bind CO 2 and enhance its reactivity for carboxylation of C(sp 3 )-H, C(sp 2 )-H and C(sp)-H bonds [ 67 ]. Statistical copolymers of styrene, 4-styryl-di(pentafluorophenyl)borane, and 4-styryl-dimesitylphosphine (feed ratio 0.8:0.1:0.1) were synthesized by RAFT polymerization ( M n = 60.8 kg·mol −1 , M w / M n = 1.18).…”
Section: Single Chain Polymer Nanoparticlesmentioning
confidence: 99%
“…More recently, SCPNs were reported that efficiently bind CO 2 and enhance its reactivity for carboxylation of C(sp 3 )-H, C(sp 2 )-H and C(sp)-H bonds [ 67 ]. Statistical copolymers of styrene, 4-styryl-di(pentafluorophenyl)borane, and 4-styryl-dimesitylphosphine (feed ratio 0.8:0.1:0.1) were synthesized by RAFT polymerization ( M n = 60.8 kg·mol −1 , M w / M n = 1.18).…”
Section: Single Chain Polymer Nanoparticlesmentioning
confidence: 99%